ANALISIS PSIKOLOGI SASTRA NOVEL GELOMBANG LAUTAN JIWA KARYA ANTA SAMSARA - Yulia Utami Putri, Ni Putu (Humanis; Volume 15. No.2. Mei 2016, 2016)
This study aims to analyze and understand the personality of characters in the novel aspect of the soul an ocean wave. Soul novel ocean waves are used as research objects were analyzed using structural theory, psychology literature, and schizophrenia. Analyzed within a builder structural elements of the story, namely a plot character and background. In this case the psychological literature is analyzed in terms of the characteristic of personality disorders
Keywords: structural theory, psychology literature, and schizophrenia